2020
DOI: 10.3390/agriculture11010002
|View full text |Cite
|
Sign up to set email alerts
|

Suitability of Composting Process for the Disposal and Valorization of Brewer’s Spent Grain

Abstract: The brewing industry is characterized by the large production of by-products. Following the fundamentals of a circular economy, several attempts to recycle brewers’ spent grain (BSG) have been investigated. However, little information is available on its use for composting. Considering the main parameters required for optimal development of composting, the objective of the present review was to analyze the literature to determine whether the microbial and physicochemical characteristics of BSG make it suitable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 79 publications
2
17
0
Order By: Relevance
“…It was reported that around 3.4 and 4.5 million tons of BSG were produced from the brewing industry in Europe and the United States, respectively [14]. The huge quantities of BSG generated in the breweries, their low market value, their high moisture content associated with a difficulty in their storage, and their bad environmental effect made their disposal challenging [72]. The market price of BSG (40.23 USD/ton) is lower than the price of other cellulosic crops (between 50 and 150 USD/ton), which is mainly because BSG have high moisture content and are sold as is [14].…”
Section: Bsg Supply Chain Systemmentioning
confidence: 99%
“…It was reported that around 3.4 and 4.5 million tons of BSG were produced from the brewing industry in Europe and the United States, respectively [14]. The huge quantities of BSG generated in the breweries, their low market value, their high moisture content associated with a difficulty in their storage, and their bad environmental effect made their disposal challenging [72]. The market price of BSG (40.23 USD/ton) is lower than the price of other cellulosic crops (between 50 and 150 USD/ton), which is mainly because BSG have high moisture content and are sold as is [14].…”
Section: Bsg Supply Chain Systemmentioning
confidence: 99%
“…The third and last phase is a maturing stage, which is characterized by the decrease in the temperature to the mesophilic range, a slower decomposition rate of the remaining recalcitrant substrates and the enrichment of the compost in humic substances (i.e., humification) [1,11]. Proteobacteria, Firmicutes, Bacteroidetes and Actinobacteria, among Bacteria, and Ascomycota, among Fungi, have shown to be the predominant groups during composting processes, with their relative abundances changing depending on the starting materials and the type of composting procedure [15][16][17]. The duration of the composting process is highly variable, ranging from two months (for easily degradable wastes) up to several years (for highly recalcitrant materials).…”
Section: Composting and Anaerobic Digestionmentioning
confidence: 99%
“…Eighty-six yeasts and bacteria species of the MGA-UNISS collection, genetically and phenotypically characterized, are included in the MBDS catalogue, starting from the first isolations dating back to 1965 until today. These are mainly yeasts isolated from food and environmental matrices such as olives and olive oil, milk and cheeses, grapes, wine and must, fish, shellfish, meat, soil, and by-products of beer processing such as brewers' spent grain and wastewater [42][43][44]. As for bacteria, since 2012, 91 strains belonging to 36 species have been isolated, genetically characterized, and divided into 50 different biochemical profiles.…”
Section: Uniss Collectionmentioning
confidence: 99%